2009
DOI: 10.1111/j.1740-0929.2009.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ‘Five freedoms’ environmental enrichment on the welfare of calves reared indoors

Abstract: We provided comfortable resting areas in pens and tools for self-grooming and suppressing aggressive behavior for environmental enrichment in Japanese black and Japanese Shorthorn calves. At the start of the experiment, the black calves (n = 10) were 164 days old and 138 kg in weight, and the Japanese Shorthorn calves (n = 10) were 176 days old and 164 kg in weight. Calves of each breed were divided into two groups (the enrichment group and the non-treatment group), and each group was housed in a 4 m x 7.2 m p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 15 publications
0
33
2
Order By: Relevance
“…Phillips and Rind (2001) reported that the daily sleeping time of Holstein-Friesian cows fed different feeding frequency ranged from 63 to 75 min/day. Ninomiya and Sato (2009) reported that Japanese Black calves slept about 20 min in conventional pen and about 40 min in enriched pen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phillips and Rind (2001) reported that the daily sleeping time of Holstein-Friesian cows fed different feeding frequency ranged from 63 to 75 min/day. Ninomiya and Sato (2009) reported that Japanese Black calves slept about 20 min in conventional pen and about 40 min in enriched pen.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies about cow's sleep under experimental condition (Fukasawa, Komatsu, & Higashiyama, ; Fukasawa, Komatsu, Higashiyama, & Oshibe, ; Krohn & Munksgaard, ; Ninomiya & Sato, ; Norring, Valros, & Munksgaard, ; Phillips & Rind, ; Ruckebusch, ). However, there is not on farm study about cow's sleep because the sleep observation on farm can be a difficult and impractical task due to the following reasons: (a) most cattle sleep during night (Ruckebusch, ); (b) sleep bouts can be short (Ruckebusch, ); and (c) the presence of an observer could affect natural sleep behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, accelerometers are widely used for monitoring posture and behavior of animals because of their low cost and small size (Watanabe et al 2005;Ledgerwood et al 2010;Hokkanen et al 2011). In this study, sleeping posture is defined as the posture that cattle adopt with their neck relaxed and their head against their flank in a lying position, as reported in several previous studies (Ruckebusch 1975;Phillips & Rind 2001;Ninomiya & Sato 2009;Norring et al 2012) (Figure 1). They used an accelerometer mounted on the neck to detect sleeping and lying time of calf, although not for adult cattle.…”
Section: Introductionmentioning
confidence: 93%
“…However, the factors that make a particular habitat valuable, such as structural complexity, may vary for individuals differing in dominance status. The presence of physical complexity within a habitat can impede visibility (Clayton, ; Eason & Stamps, ), or movement (Deboom & Wahl, ; Loss et al, ; Radabaugh, Bauer, & Brown, ); as a result, resource monopolization (e.g., Basquill & Grant, ) and aggressive behaviour are often lower in complex than open habitats (Batzina & Karakatsouli, ; Chaloupkova, Illmann, Bartos, & Spinka, ; Corkum & Cronin, ; Danley, ; Ninomiya & Sato, ). Consequently, more aggressive competitors may experience increased competitive success in open habitats, but smaller, less competitive individuals are more often found in habitats with more habitat complexity (Gibb & Parr, ; Höjesjö, Johnsson, & Bohlin, ).…”
Section: Introductionmentioning
confidence: 99%